On the particularities of deviant behaviour in the case of alcoholism connected to alexithymia - Avin, Alexander I. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
Deviant behaviour of people addicted to alcohol is one of the most acute social problems. The main characteristics of deviant behaviour in the case of alcoholism are alterations of personality, psychological defence mechanisms and alexithymia as a prerequisite of misunderstandings and interpersonal conflicts. In order to demonstrate the link between the propensity for conflict in the case of alcoholism and the alexithymia with psychological defence mechanisms we have conducted an empirical case study with 86 respondents suffering from alcohol addiction and 72 respondents of the same age without any history of alcohol abuse. Our case study was based on the TAS (Toronto Alexithymia Scale), on the LSI (Life Style Index) and Conflict Behaviour questionnaires. The study has revealed the connection between alcohol addiction and alexithymia. Alexithymia-affected individuals suffering from alcohol addiction are more likely to demonstrate such psychological defence mechanisms as «projection» and «regression», as well as avoid confrontations and arguments. All the behavioural patterns of alexithymia-affected individuals in conflict situations should be considered in correctional psychology programs which are aimed at helping this group of individuals to develop emotional and behavioural self-regulation.
Keywords: alcohol addiction; conflict behaviour; alexithymia; psychological defence mechanisms